IMPLEMENTASI KEBIJAKAN PENANGANAN INFEKSI LATEN TUBERKULOSIS (ILTB): ANALISIS TANGGUNG JAWAB PEMERINTAH DALAM PENYEDIAAN OBAT DI KABUPATEN KAMPAR - Wirda Susanti; Ardiansah Ardiansah; Yeni Triana (Jurnal Ilmiah Advokasi, 2025)
This study aims to analyze the implementation of the Latent Tuberculosis Infection (LTBI) management policy and the government’s responsibility in providing medication for household contacts of tuberculosis patients in Kampar Regency. The study refers to Presidential Regulation Number 67 of 2021 on Tuberculosis Control and Minister of Health Regulation Number 67 of 2016 as the primary normative framework governing policy implementation. The research employs a socio-legal (empirical legal) approach to assess the conformity between legal norms and their practical implementation in the field. Data were collected through interviews with healthcare workers, families of TB patients, and local policymakers, supported by observations at healthcare facilities. The findings indicate that the local government has undertaken efforts to provide LTBI medication in accordance with technical guidelines; however, implementation remains constrained by structural and cultural barriers, including limited trained healthcare personnel, challenges in drug distribution, and low public awareness regarding the importance of preventive therapy. The study recommends strengthening cross-sector coordination, enhancing the capacity of healthcare personnel, and developing sustainable public education strategies to ensure the effectiveness of LTBI policy implementation and the fulfillment of the state’s responsibility in protecting public health.Keywords: Policy Implementation, Latent Tuberculosis Infection, Government Responsibility, Drug Provision